Effect of silica particle size on macrophage inflammatory responses. - Toshimasa Kusaka; Masafumi Nakayama; Kyohei Nakamura; Mai Ishimiya; Emi Furusawa; Kouetsu Ogasawara (PLoS ONE)
Amorphous silica particles, such as nanoparticles (<100 nm diameter particles), are used in a wide variety of products, including pharmaceuticals, paints, cosmetics, and food. Nevertheless, the immunotoxicity of these particles and the relationship between silica particle size and pro-inflammatory activity are not fully understood. In this study, we addressed the relationship between the size of amorphous silica (particle dose, diameter, number, and surface area) and the inflammatory activity (macrophage phagocytosis, inflammasome activation, IL-1β secretion, cell death and lung inflammation). Irrespective of diameter size, silica particles were efficiently internalized by mouse bone marrow-derived macrophages via an actin cytoskeleton-dependent pathway, and induced caspase-1, but not caspase-11, activation. Of note, 30 nm-1000 nm diameter silica particles induced lysosomal destabilization, cell death, and IL-1β secretion at markedly higher levels than did 3000 nm-10000 nm silica particles. Consistent with in vitro results, intra-tracheal administration of 30 nm silica particles into mice caused more severe lung inflammation than that of 3000 nm silica particles, as assessed by measurement of pro-inflammatory cytokines and neutrophil infiltration in bronchoalveolar lavage fluid of mice, and by the micro-computed tomography analysis. Taken together, these results suggest that silica particle size impacts immune responses, with submicron amorphous silica particles inducing higher inflammatory responses than silica particles over 1000 nm in size, which is ascribed not only to their ability to induce caspase-1 activation but also to their cytotoxicity.